Ground‐Truthing a Recent Report of Cover Crop–Induced Winter Warming. Issue 1 (1st April 2019) - Hunter, Mitchell C.; White, Charles M.; Kaye, Jason P.; Kemanian, Armen R.
Abstract : Core Ideas: It was recently reported that cover crops could raise winter temperature up to 3°C. Agronomic context and measured cover crop morphology indicate this is unlikely. The most realistic cover crop scenario did not cause significant local warming. Winter cover crops remain a potential tool for climate mitigation. Winter cover crops have been proposed as a potential climate mitigation practice, but a recent study concluded that cover crops may increase local temperature by up to 3°C. Here, we present agronomic context and data on cover crop morphology to ground‐truth the scenarios simulated in this study. We conclude that the scenario of cover crop morphology on which the study's headline claim is based is unlikely to be found in contemporary production systems. The most realistic scenario simulated did not result in significant local warming. Therefore, we argue that widespread planting of cover crops is unlikely to substantially increase local winter temperatures.